2006
DOI: 10.2174/138920206778426951
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Differences Between Normal and Malignant Cells as a Basis for Treatment of Intracerebral Neoplasms Using a DNA-Based Vaccine

Abstract: Antigenic differences between normal and malignant cells of the cancer patient form the rationale for clinical immunotherapeutic strategies. Because the antigenic phenotype of neoplastic cells varies widely among different cells within the same malignant cell-population, immunization with a vaccine that stimulates immunity to the broad array of tumor antigens expressed by the cancer cells is likely to be more efficacious than immunization with a vaccine for a single antigen. A vaccine prepared by transfer of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The immune surveillance of the intracellular proteome of all nucleated cells is carried out by the major histocompatibility complex (MHC) class I system, commonly known as the human leukocyte antigen (HLA) system [19]. Antigen peptide presentation distinguishes between malignant or infected cells and their healthy counterparts, resulting in the creation of abnormal cells that serve as the basis for identification [20]. Therefore, the 16-kDa peptide MHC can give precise diagnostic and therapeutic targets for latent MTB infection.…”
Section: Discussionmentioning
confidence: 99%
“…The immune surveillance of the intracellular proteome of all nucleated cells is carried out by the major histocompatibility complex (MHC) class I system, commonly known as the human leukocyte antigen (HLA) system [19]. Antigen peptide presentation distinguishes between malignant or infected cells and their healthy counterparts, resulting in the creation of abnormal cells that serve as the basis for identification [20]. Therefore, the 16-kDa peptide MHC can give precise diagnostic and therapeutic targets for latent MTB infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that transfection of genomic DNA from the malignant cells into a fibroblast cell line resulted in stable integration and expression of the transferred DNA [Cohen, 2001;Lichtor et al, 2005;Lichtor et al, 2006;Lichtor et al, 2008]. Both the genotype and the phenotype of the cells that took up the exogenous DNA were altered as portions of the transferred DNA were expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern related to therapy with DNA-based vaccines is that genes specifying normal "self" antigens are likely to be expressed by the DNA-transfected cells, creating a danger that autoimmune disease might develop, although this has not been observed thus far. Inbred mice immunized with the DNA-based vaccine or tumor-bearing mice injected with therapeutic DNA-based vaccines failed to exhibit adverse effects [Lichtor et al, 2006]. Of course, protocols that depend upon the use of tumor cell-extracts, peptide eluates of tumor cells, fusion cells, cDNAs or RNAs derived from tumor cells are subject to the same concern.…”
Section: Disadvantages Of Transfer Of Tumor-derived Dna Transfer Intomentioning
confidence: 99%
“…Successful immuno-therapies for intracerebrally metastasizing breast cancer have previously been reported with interleukin-2-secreting fibroblasts [6], various interleukin (IL) secreting syngeneic/allogeneic fibroblasts transfected with DNA from breast cancer cells [7][8][9], and syngeneic/allogeneic fibroblasts transfected with cDNA from spontaneously arising breast cancer cells [10]. The efficacy was compared in combined immunotherapy with paclitaxel [11].…”
Section: Introductionmentioning
confidence: 99%